Desain Stand Al-Qur’an Untuk Imam Sholat - Andi Farid Hidayanto; Rausan Apriliannor (Jurnal Desain Indonesia., 2021)
Remembering memorizing the Qur'an takes time, and when in the process of memorizing someone encounters obstacles, it takes motivation or encouragement, both internal and external motivation. This also applies to the imam of the prayer when he is the imam of his congregation. Sometimes the memorization of the surah is disturbed, and the congregation sometimes cannot help the imam memorize the surah because he does not memorize the surah he reads. From these problems, a product facility is needed that helps make it easier for the Imam to pray in reciting the reading of the Qur'an in prayer in the form of an al-Qur'an booth. The existing Qur'an booth products use heavy materials with unattractive shapes. The material used is Dutch teak wood, which is softer than other wood varieties. Dutch teak is resistant to shock. By using the Vinod Goel method, This design process includes three stages, namely Prelimenary Design in the form of existing, problem formulation, data analysis, design specifications, Design Development in the form of sketches and design development, and Final Design in the form of technical drawings, 3D Modeling, prototypes, posters and portfolios. The design of this product produces a booth product where the Koran is placed so that the imam can read the Koran in prayer, thus helping memorization when he becomes the imam of praying at the mosque.